Strategi Pengelolaan Ekowisata Mangrove Berbasis Konservasi pada Objek Wisata Alam Trekking di Tahura Ngurah Rai, Bali - Atsna Qi Doma T. Manihuruk; I Wayan Restu; I Wayan Darya Kartika (Current Trends in Aquatic Science, 2021)
The aim of this research was to explain the legal aspects of trekking nature tourism object, to determined the zones of this place existence and to explain the strategies management of mangrove ecotourism in trekking nature tourism object. The methods of this research were using survey, purposive sampling and accidental sampling. The data were analized using a content analysis and SWOT analysis. The results indicates that the development of that place has already been legal as the tourist attraction. This statement is according to the decree of the Minister of Forest Number 544/Kpts-II/1993 on September 25, 1993. The development of this place is also on the right zone, the place is located in the utilization zone. And, this research resulted 6 strategies namely; improved the infrastructure and providing dustbins, toilet revitalitation and reconstruction the bridges, conduct waste management with an integrated system which is based on community management that involved people around the place, increasing the diversification of tourist attraction objects, increasing the promotion by joining the tourism developers. The last but not least, is about issuance of PERDA (Peraturan Daerah) to control and made an ideal price for tickets, and improved the human resource management.